Genetic characteristics of HA gene of influenza A (H1N1) virus isolated from severe and fatal infection cases in Guizhou province in 2019 - Lijuan REN; Qinni ZHENG; Li ZHUANG; Weijia JIANG; Yonghu WAN (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo analyze characteristics and specific molecular sites of hemagglutinin (HA) gene of influenza A (H1N1) virus isolated among severe and deadly infection cases in Guizhou province in 2019 for providing evidence to influenza prevention and control in the province. MethodsInfluenza A (H1N1) virus strains were isolated from 28 nasopharyngeal swab specimens collected from severe and fatal infection incidents in the province during 2019. HA genes of the 13 isolated viral strains were amplified and sequenced. Bioinformatics analysis was performed on the HA genes using existing sequence of strains in mild cases and reference sequences from National Center of Biotechnology Information (NCBI) or the Global Initiative on Sharing Avian Influenza Data (GISAID). ResultsThe homology of the nucleotide and amino acid sequences are 98.0% - 100.0% and 97.9% - 100.0% among the isolated virus strains and the strains belong to different secondary branches. In comparison with those of the vaccine strain of 2019 and previous years, the homology of the nucleotide/amino acid sequences of the isolated strains are 98.2% - 99.3%/97.1% - 98.4% and 98.1% - 98.9%/97.5% - 98.7%, respectively. Contrasted to those of mild infection cases, a total of 12 gene locus mutations were identified in the isolated virus strains and V312I was a common locus of the mutations. Antigen determinant mutations in 3 gene regions were identified, with 2 simultaneous mutations among loci of strains QNZ2019YYX and BJ2019WXP. ConclusionThe homology of HA gene sequences is high between influenza A (H1N1) virus strains isolated among severe and fatal infection cases in Guizhou province and the vaccine strain in 2019. Mutations of the isolated virus strains involved two antigen determinants and the strains may be novel variants. The mutant V312I may be a specific locus for pathogenicity of the isolated virus strains.